Penerapan Metode Pembelajaran Ctl (Contextual Teaching And Learning) Dapat Meningkatkan Pemahaman Konsep Perkalian Dasar Pembelajaran Mapel Matematika Pada Siswa Kelas Ii Semester II Sd N Tlutup Kecamatan Trangkil Pati 2014/2015 - Karniti Jumiatin, Endang, Dra. Sri Gunarsi, S.H., M.H (2015)
This study is an action research to improve understanding of the basic concept of multiplication through learning methods CTL (Contextual Teaching And Learning). Data collection techniques used were observation, evaluation tests, interviews and documentation. The study was conducted in the second semester of second grade students and teachers SD N Tlutup on 2 March 2015. The research phase consists of four phases: planning, implementation, observation and reflection. Follow-transactions are carried out in two cycles, the first cycle and the second cycle with allocation of 2 x 35 minutes. The subjects of this study second semester grade II SD N Tlutup totaling 30 students, 17 boys and 13 students daughter with the object of research is the understanding of the basic concepts in learning multiplication math subject. Data analysis techniques is the data collection, data reduction, data display, and conclusion. From the results of research and discussion concluded that the application of learning methods CTL in the second semester of grade II SD N Tlutup Trangkil District of Pati regency, can improve the understanding of the basic concept of multiplication. Improvements seen from several stages of pre-cycle known basic understanding of the concept of multiplication low student with a percentage of 30%, the first cycle there is a slight increase in the percentage of 60%. Currently the second cycle students' understanding very well with a percentage of 80%. These results demonstrate an increased understanding of the basic concept of multiplication by the application of learning methods CTL (Contextual Teahing And Learning).